God’s Natural World and Modern Man’s State of Mind in William Wordsworth’s “The Tables Turned” (Al-Qamar, 2022)
The research will examine the philosophical position of William Wordsworth in the field of poetry by sketching his love for God’s natural world and nature in his adult life to prove him as a philosophical poet. The present study is carried out on the selected poem The Tables Turned written by William Wordsworth emphasizes on modern man (who only relies on science and discoveries) instead of becoming part of nature and love for nature. Moreover, the man versus God’s natural world in his poetry in general and in this poem, in particular, shows a contrasting relationship of modern man which the author observed and discussed in detail. Nature (God’s power/creature made by God and natural beauty) is a source of reasoning for modern man as mentioned in Quran Surah Al Baqra albeit modern man ignored those aspects of nature and focused only on science. The analysis shows how the revolutionary spirit and harmony with Nature can make modern man a happy person amid Nature as Nature is not only the name of landscapes but also covers all the complexity and the aspect of life and death.
Keywords: Nature; consciousness; adult life; revolutionary; spirit